1975
DOI: 10.1508/cytologia.40.557
|View full text |Cite
|
Sign up to set email alerts
|

Diploid and Tetraploid Chromosome Races in <i>Fimbristylis ovata</i> (Cyperaceae)

Abstract: Sharma and Bat (1956) and Sanyal and Sharma (1972) studied the cytology of Fimbristylis ovata (=F. monostachya (L.) Hassk.) from northern India. In the course of cytological investigations of the species of Fimbristylis from southern India, 2 populations of F. ovata (Burm. f.) Kern with different chromosome numbers have been encountered (Nijalingappa 1972). The present contribution deals with the karyotype and meiosis of the 2 populations. Materials and methodsThe materials were collected from Bangalore (Coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Chromosome number and length in 14 species of Rhynchospora. Species are organized according to Kükenthal (1949Kükenthal ( , 1950Kükenthal ( , 1951 Vanzela et al 1996Vanzela et al , 2000Luceño et al 1998), and other genera of Cyperaceae, such as Carex (Davies 1956), Isolepis (Dopchiz and Poggio 1999), Fimbristylis (Nijalingappa 1975), Scleria (Yano and Hoshino 2007) and Eleocharis (Da Silva, González-Elizondo, Rego et al 2008;Da Silva et al 2010). Our data are in agreement with Greilhuber (1995) who considers the holokinetic chromosomes a synapomorphy of Cyperaceae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosome number and length in 14 species of Rhynchospora. Species are organized according to Kükenthal (1949Kükenthal ( , 1950Kükenthal ( , 1951 Vanzela et al 1996Vanzela et al , 2000Luceño et al 1998), and other genera of Cyperaceae, such as Carex (Davies 1956), Isolepis (Dopchiz and Poggio 1999), Fimbristylis (Nijalingappa 1975), Scleria (Yano and Hoshino 2007) and Eleocharis (Da Silva, González-Elizondo, Rego et al 2008;Da Silva et al 2010). Our data are in agreement with Greilhuber (1995) who considers the holokinetic chromosomes a synapomorphy of Cyperaceae.…”
Section: Resultsmentioning
confidence: 99%
“…Initially a basic number x = 5 was proposed by Löve et al (1957) for Cypercaeae. Recently, it has been suggested for Fimbristylis (Nijalingappa 1975), Rhynchospora (Luceño et al 1998;Vanzela et al 2000) and Eleocharis (Da Silva et al 2005Silva et al , 2010Da Silva, González-Elizondo, Rego et al 2008). However, the basic numbers x = 6 and 9 were also found in Rhynchospora, which are considered secondary (Luceño et al 1998;Vanzela et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The family is well known, along with the Juncaceae, for having a suite of cytological peculiarities including: psuedomonad pollen grain development (Juel, 1900;Stout, 1913;Tanaka, 1941); diffuse kinetochores ; postreductional meiosis (Wahl, 1940); and chromosome fission and fusion, often referred to as agmatoploidy Faulkner, 1972;Hoshino, 1981a;Cayouette & Morisset, 1985, 1986a, 1986bLuceno & Castroviejo, 1991;Luceño, 1993Luceño, , 1994Luceño, et al 1998;and others). While there have been some reports of localized kinetochores in some Cyperaceae genera (Fimbristylis-Sharma & Bal (1954, Nijalingappa (1975a), and Rath & Patnaik (1977); Eleocharis- ; Scirpus-Sanyal & Sharma (1972a); Lipocarpha- ; Cyperus- ), these reports have been questioned and it has been suggested that non-localized centromeres, i.e. the diffuse kinetochore condition, is a synapomorphy for the Cyperaceae and Juncaceae clade (Greilhuber, 1995).…”
Section: Introductionmentioning
confidence: 99%